The Role of Poultry Farms and Wild Birds During 2016-2017 Avian Influenza Epizootic in Europe - TSIOURIS, V.; MAVROMATI, N.; MANTZIOS, T.; KISKINIS, K.; Sossidou, E.; GEORGOPOULOU, I. (Journal of the Hellenic Veterinary Medical Society, 2021)
Avian influenza is a contagious viral disease, affecting several species of birds, and poses a significant public threat. During 2016-2017, there were 2,224 high pathogenic avian influenza outbreaks in Europe, which led to the destruction of 9,663,770 birds, and 72 low pathogenic avian influenza outbreaks in 5 European countries, which caused 276,584 bird fatalities. The majority of the epidemics were in wild and backyard birds, except for France and Hungary, where the majority of outbreaks were in duck-goose farms. Notably, there were a total of 100 outbreaks in turkey farms and 37 outbreaks in layer farms, while in broiler farms there were only 10. It is indisputable that wild birds are natural hosts and reservoirs for all types of avian influenza viruses. However, the role of poultry farms on the AI intra-country epidemiology has not been fully clarified. Based on the official reports of OIE for AI, this study indicates that poultry farms, especially fattening turkey and layer chicken farms, are high-risk factors concerning the introduction of the disease into an area and its spread into other poultry farms.